Pelatihan Pembelajaran Inovatif Tipe STEAM Bagi Guru-Guru SD YAPIS II Merauke - Muh. Rafi'y; Ferry Irawan; Salman Alparis Sormin (Yayasan Perguruan Kampus, 2023)
Education is an important basis in forming superior human resources in a region. Very rapid changes in the 21st century require educators to be more skilled in fulfilling the competencies needed to transfer knowledge to their students. There are so many models, methods and approaches offered in the learning process, one of which is the STEAM approach (Science, Technology, Engineering, Art and Mathematics). In implementing PkM, the aim is for educators to be able to recognize, understand and apply the STEAM approach. This service was carried out at SD YAPIS II Merauke and was attended by 15 teachers. This activity begins with giving a pretest, then explaining the STEAM material, following up plans and giving a posttest. The result of this PkM is that teachers understand more about the STEAM approach and are ready to apply it to classroom learning so that in the future teachers are expected to be more proactive about changes that occur and continue to upgrade themselves to be more adaptive to various ongoing learning paradigms. continues to develop over time.